Theory of planned behavior and whistleblowing intention - Tarjo Tarjo; Anang Suwito; Ifa Diah Aprillia; Greska Redielano Ramadan (University of Merdeka Malang, 2019)
This research examined the theory of planned behavior (TPB) as predictor whistleblowing intention. According to TPB, it is difficult to posit whistleblowing as actual behavior. Whistleblowing is more suited to be posited as intention. Intent means the likelihood of actual behavior occurred. We examined attitude, subjective norms, and perceived behavioral control as TPB variables. We also investigated a few control variables such as colleagues support, organizational support, and fear of retaliation. The online survey was conducted in obtaining data by a web-based questionnaire. Participants of this survey were employees of regional owned east java bank. The number of respondents was 112 employees from all departments and units. Validity, reliability, regression, and path analysis were used in testing research instrument and several hypotheses. The result showed that attitudes and subjective norms as TPB variables have a significant impact on whistleblowing intention. However, perceived behavioral control does not affect whistleblowing intention. While, among several control variables, only fear of retaliation that has a significant effect on whistleblowing intention. Furthermore, this study also found empirical evidence that knowledge and subjective norms have an indirect effect on whistleblowing intention through attitudes. This research suggests that regional owned east java bank should provide an environment and channels to support whistleblowing within effectively, especially through protection and/or reward systems, or etc.JEL Classification: D23, G34, L23DOI: https://doi.org/10.26905/jkdp.v23i1.2714